غه‌نيمه له‌ ژێر ڕۆشنایی ده‌قه‌كانی قورئان و فه‌رمووده‌دا - كانبی, سه‌رپه‌رشتیار: پ. د. صلاح; نادر, خوێندكاری دكتۆرا: م. سه‌عيد مولود (Sulaimani Journal for Humanities, 2023)
Following the muslims’ immigration to Madina, taking Ghanīmah (spoils of war) as a religious and social practice became a necessity for the Islamic society due to the economic crisis that the Muslims were facing. That was because, on the one hand, the Quraysh had seized the wealth and properties of the muslims in Mecca, and because, on the one hand, the number of people living in the city of Medina was increasing rapidly. Ghanīmah helped to solve the financial crisis the Muslims were facing, and it also became a motivation for certain Arab tribes to convert to Islam because were struggling to live and survive in the inhospitable Arabian Peninsula. Due to its significant importance, the notion of Ghanīmah has been widely addressed in Islamic sources especially those sources that are concerned with Islamic economics. The Islamics scholars and jurists have paid a great attention to Ghanīmah because of its impact on their society and the remarkable transformation it brought to that geographically isolated part of the world and making it more open politically and socially to the outside world.